A Study of Revenue Management of Tirumala Tirupati Devasthanam: Management Control of Religious Trust in India (The Gaze: Journal of Tourism and Hospitality, 2020)
Management control is associated with the institutionalization of trust inside an organization. It is a control of economic and administrative functionalities like revenue management, future plans to expand income, target-setting as well as public facilities and amenities. Pilgrimage tourism is a fast-growing service industry in modern India, and the majority of them are Hindu because more than 80% of Indian people believe in Hindu. Tirumala Tirupati Devasthalnam (TTD) stands to be the biggest religious trust in India. On this background, this study will clarify the two aspects of the management control of TTD: (i) revenue management and commercial profit,(ii) economic and business impact to the local community. Based on the secondary data, this study focused on revenue management of TTD. First, the author explored that TTD has created a religious market around the world. The excellent management control of TTD with the help of IT in the present period changed into one of the richest temples of Hindu religion. The trust started the pricing of religious objects; changes in marketing policies, diversification strategies, and use of IT lead its success. Second, it explains the idea that the economic impacts and revenue management of pilgrimage tourism with the example of the TTD. Due to the increasing number of pilgrimages in the area, the number of population is increasing, and social infrastructure is also developing. Based on the study result, this study suggests that to establish a new revenue management system/team.